THE ROLE OF COUNSELING TEACHERS BASED ON THE CURRICULUM FREEDOM TO LEARN - Elfira, Yenni; Mudjiran, Mudjiran; Nirwana, Herman; Karneli, Yeni (Widyagogik, 2022)
This paper aims to determine the role of guidance and counseling teachers based on the “Merdeka Belajar” curriculum. This writing uses a qualitative research method which is a literature study. The concept of the curriculum "Merdeka Belajar" is the freedom of learning for BK teachers to be free to think, innovate, and be creative. The expected evaluation is that it can provide comfort in the learning process.